2021
DOI: 10.1021/acsami.1c00879
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable and Healable Conductive Elastomer Based on PEDOT:PSS/Natural Rubber for Self-Powered Temperature and Strain Sensing

Abstract: Self-powered elastic Conductors based on thermoelectric materials with the ability to harvest energy from the living environment are considered as important for electronic devices under off-grid, maintenance-free, or unfeasible battery replacement circumstances. Poly(3,4-ethylenedioxythiophene)-poly-(styrenesulfonate) (PEDOT:PSS) is perhaps the most well-known organic conductor. However, the application of PEDOT:PSS in flexible devices is limited by its brittleness and various unrecoverable properties under st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 47 publications
(46 reference statements)
0
77
0
Order By: Relevance
“…On account of considering to enhance both stretchability and thermoelectric performance, Yang et al proposed a composite film incorporating PEDOT:PSS treated by EG and DMSO with natural rubber (NR), then treated by water and phosphatebuffered saline to realize strain and conductivity recovery (Figure 3a). [43] The composite film with 10 wt% PEDOT:PSS possessed electrical conductivity of 4.1 S cm −1 and 31 µV K −1 Seebeck coefficient (Figure 3b). The composite film exhibited brilliant strain sensing performance at even 100% tensile strain (Figure 3c) and presented wrinkles under the free state due to the interlacing of rubber particles.…”
Section: Blending With Elastic Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…On account of considering to enhance both stretchability and thermoelectric performance, Yang et al proposed a composite film incorporating PEDOT:PSS treated by EG and DMSO with natural rubber (NR), then treated by water and phosphatebuffered saline to realize strain and conductivity recovery (Figure 3a). [43] The composite film with 10 wt% PEDOT:PSS possessed electrical conductivity of 4.1 S cm −1 and 31 µV K −1 Seebeck coefficient (Figure 3b). The composite film exhibited brilliant strain sensing performance at even 100% tensile strain (Figure 3c) and presented wrinkles under the free state due to the interlacing of rubber particles.…”
Section: Blending With Elastic Materialsmentioning
confidence: 99%
“…d) Surface SEM images of 10 wt% composite films under various tensile strains. e) Morphology deformation of the composite films under tensile strain.Reproduced with permission [43]. Copyright 2021, American Chemical Society.…”
mentioning
confidence: 99%
“…For example, Qiu et al [88] reported a dual-mode sensor based on interlocked piezoresistive and piezoelectric films, realizing the complementary performance of the two sensing mechanisms, and thus improving the sensitivity and broadening the sensing range [Figure 5A]. Hwang et al [89] reported a transparent sensor combining piezoresistive and capacitive transduction mechanisms, which can distinguish touch and pressure, as shown in Figure 5B. Besides the direct combination of two sensing mechanisms in a single device design, a single sensor can respond to a variety of stimuli by selecting specific functional materials.…”
Section: From Single-mode Sensor To Multi-mode Tactile Sensormentioning
confidence: 99%
“…(B) Schematic diagram and current versus time of the transparent dual-mode sensor, which can distinguish touch and pressure. Reproduced with permission from Ref [89]. .…”
mentioning
confidence: 99%
“… 34 Such polymer based composites are generally fabricated using in situ , chemical oxidation, vapor phase polymerization, and chemical exfoliation, 35–37 whereas the filler are widely mixed with different organic solvents, reducing agents, dispersing agents and stabilizers. 38 The features of the intrinsic conductive polymers are not only limited to their potential electrical and thermal properties but due to their light weight, flexibility and higher stability against water, and air makes them highly suitable for super capacitors, batteries, solar cells, and other energy storage and harvesting devices. 39 Furthermore, chemical functionalization and in situ solution processed polymer composite are commonly used including screen printing, ink jet printing dispenser printing; spray printing, and spin coating, 40,41 as an efficient, cost-effective method to fabricate TE devices on mass scale.…”
Section: Introductionmentioning
confidence: 99%